Perlindungan Hukum Terhadap Masyarakat Adat Menurut The United Nations Declaration On The Rights Of Indigenous Peoples - DANIEL S NABABAN; Emilda Firdaus; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Issues of recognition of Indigenous People (which by the international world is translated by the term Indigenous Peoples (Ips) is a problem that has developed since Ke century - XIV. Indigenous Peoples (Ips) naturally have a genuine autonomy (original autonomous powers) and rights to land (entitlesmens to land). ILO Convention 107 of 1957 concerning Indigenous and Tribal Nations that assumes that the Indigenous People is the poorest people (Uncivilized Society) to be developed into a modern society. Protection of Land Rights of Indigenous People in the United Nations Declaration on Rights of indigenous peoples are reflected in Article 26, while the Protection of Land Rights of Indigenous People in Indonesia has been poured into the form of legislation relating to the recognition of Indigenous People in Indonesia. Terms of recognition of customary law communities along with their traditional rights is a form of acceptance tertinggi.Sampai state as an organization of power today, customary rights arrangements still sporadically scattered in various laws - laws in Indonesia, all of which are aimed at providing legal protection ofJOM Fakultas Hukum Volume 2 Nomor 2 Oktober 2015 2customary rights. But it becomes unclear and cause various interpretations which are not adequate with the aim, often negating the detriment of the rights of Indigenous People. As for some of the problems related to communal rights are concerned: Management Rights for Indigenous People and Land Rights Alliance for Indigenous People. Keywords: Indigenous People - Land Rights